The use of social media for earthquake and Tsunami information - Handayani, Anik Nur; Suciati, Reski Dwi; Qomaria, Ulfa; Lestari , Widya; Nugraha, Youngga Rega; Machumu, Paul Igunda (Bulletin of Social Informatics Theory and Application, 2023)
As one of the countries being passed by the Pacific Fire Circle (Ring of Fire), Indonesia is prone to earthquakes. Recently, an earthquake and tsunami occurred. A new disaster occurred in Central Sulawesi, Indonesia, resulting in the destroyed buildings and houses. This occurrence of the disaster was quite shocking to various countries. News of the occurrence of natural disasters immediately went viral through various social media due to the residents' and BMKG's posts. Social media is greatly involved in natural disaster cases as it facilitates analysis on the conditions and situations of earthquake-affected areas. Besides, it also functions to disseminate earthquake information. By using social media, such as Twitter and Facebook, we may rescue the directly affected individuals. It can also be means of sharing information and ways for people in and outside disaster-affected areas to volunteer and provide support-based information to affected individuals. Additionally, social media can perform important assistance functions such as identification of safety, placement of displaced people, provision of damage information, support for disabled people, volunteer organizations, fundraising, and a moral support system. This study discusses the potential usage of social media in disaster preparedness and response, especially in Central Sulawesi, Indonesia, earthquakes and tsunamis.